Navigating Cancel Culture in Indonesia: Understanding Cyberbullying and Social Control in Viral Cases (September-November 2023) - Alfin Nur Laili; Pudjo Suharso; Sukidin Sukidin (Universitas Andalas, 2024)
Cancel culture is a phenomenon that creates space for individuals to voice opinions and evaluate behavior that is considered to violate values and norms. Cancel culture can move in two directions, Cyberbullying and Social control. To study cancel culture in Indonesia, there are 5 viral cases (September-November 2023), namely: (1) The case of Pandawara's feud with the Loji Sukabumi Beach government, (2) The ice-cream case by Oklin Fia, (3) The case of abuse committed by members' children. DPR RI, (4) Case of bullying of Cilacap Middle School students, (5) Case of Palestine and Israel. This research explores the direction of cancel culture in Indonesian society, the role of social media and its impact. Using netnography, ten informants were interviewed, and sentiment analysis on Instagram and Analysis using the Naive Bayes model shows that of the 10 social media platforms, 8 of them are cyberbullying and the other 3 are social control. Social media acts as a catalyst for cancel culture in the rapid dissemination of information and the formation of public opinion. The consequences of cancel culture include boycotts, decreased product sales, and prolonged online debates. Frequent misinformation and the instantaneous nature of social media trigger cancel culture, especially cyberbullying, which results in material and mental health losses.